The Role of Bakhtiari Women in the Development of Tourism and Local Economy, with an Emphasis on Social Entrepreneurship and Traditional Clothing Production in Sustainable Paradigm - Soheila Khosravi; Roshanak Davari (زن در فرهنگ و هنر)
One of the objectives of this field is to foster the empowerment of women and the development of local economies through a variety of methods, such as social entrepreneur​ship, within the framework of sustainable development. The aim of this study is to investigate and analyze the role of Bakhtiari women in the development of the local economy and tourism in Iran, with a particular focus on the significance of social entrepreneurship and the production of traditional Bakhtiari clothing as critical factors in this development. Qualitative and quantitative methodologies were implemented in this investigation. Questionnaires and field interviews with residents of Chaharmahal and Bakhtiari provinces, as well as library research, have been implemented to gather data. The statistical population consists of Bakhtiari women, with a sample size of 389 individuals, and data analysis was conducted using statistical methods and analytical models. The results of this study indicate that the Bakhtiari women have a significant impact on the tourism and local economy. Through social entrepreneurship, they address the creation of employment opportunities and the development of local economic activities. The primary occupation of the Bakhtiari people is the production of traditional apparel, which plays a unique role in the empowerment of women and the promotion of cultural and historical tourism in the designated regions. Based on the findings, the development of social entrepreneurship and the production of traditional apparel can contribute to the improved welfare of individuals in these communities and local areas. A suitable step toward attaining sustainable development goals can be taken by considering this matter and taking appropriate measures to support and develop these activities in local policy-making and planning.